Microwave-assisted synthesis of 7-azaindoles via iron-catalyzed cyclization of an o-haloaromatic amine with terminal alkynes. Issue 68 (2nd December 2019) - Le, Yi; Yang, Zhisong; Chen, Yumei; Chen, Dongmei; Yan, Longjia; Wang, Zhenchao; Ouyang, Guiping
Abstract : An efficient and practical procedure was developed to prepare 7-azaindole, starting from an o -haloaromatic amine and corresponding terminal alkynes under microwave irradiation and the scope was demonstrated with a number of examples. Abstract : An efficient and practical procedure was developed to prepare 7-azaindole, starting from an o -haloaromatic amine and corresponding terminal alkynes under microwave irradiation and the scope was demonstrated with a number of examples. The valuable features of this procedure included the iron-catalyzed cyclization, short reaction times and convenient operation. Furthermore, iron catalysis is an interesting alternative to homogeneous catalysis for the synthesis of heterocycles.